2004
DOI: 10.1128/jvi.78.6.3140-3144.2004
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Low-Dose Mucosal Simian Immunodeficiency Virus SIVmac239 Challenge Results in the Same Viral and Immunological Kinetics as High-Dose Challenge: a Model for the Evaluation of Vaccine Efficacy in Nonhuman Primates

Abstract: Simian immunodeficiency virus (SIV) challenge of rhesus macaques provides a relevant model for the assessment of human immunodeficiency virus (HIV) vaccine strategies. To ensure that all macaques become infected, the vaccinees and controls are exposed to large doses of pathogenic SIV. These nonphysiological high-dose challenges may adversely affect vaccine evaluation by overwhelming potentially efficacious vaccine responses. To determine whether a more physiologically relevant low-dose challenge can initiate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 29 publications
0
67
0
Order By: Relevance
“…In contrast to the outcome of the RV144 human trial, protection from SHIV acquisition was not achieved; however, this may reflect the single high-dose intravenous challenge used here in the nonhuman primate protocol. Others have suggested that a repetitive low-dose challenge is more comparable to the human situation (37,46,62), and in fact protection from systemic infection following repeated lowdose challenge has been demonstrated with some immunized macaques (33). Protective efficacy elicited by our replicating Ad-recombinant prime/envelope boost regimen against a repetitive low-dose challenge will be evaluated in future preclinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the outcome of the RV144 human trial, protection from SHIV acquisition was not achieved; however, this may reflect the single high-dose intravenous challenge used here in the nonhuman primate protocol. Others have suggested that a repetitive low-dose challenge is more comparable to the human situation (37,46,62), and in fact protection from systemic infection following repeated lowdose challenge has been demonstrated with some immunized macaques (33). Protective efficacy elicited by our replicating Ad-recombinant prime/envelope boost regimen against a repetitive low-dose challenge will be evaluated in future preclinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…SIV vaccine models should faithfully model the biology of HIV-1 acquisition (1). To mimic HIV-1 transmission, current SIV-based nonhuman primate vaccine approaches, including those studied here, generally utilize a low-to moderate-dose repeat mucosal challenge with a viral quasispecies, such as neutralization-sensitive SIVsmE660 or neutralization-resistant SIVmac251 (124,125). SIVsmE660 serves as a heterologous challenge virus for SIVmac239 immunogens, because, unlike SIVmac251, it is genetically distinct from SIVmac239.…”
Section: Discussionmentioning
confidence: 99%
“…[56][57][58] By reducing initial HIV viral replication, PrEP might convert a strong HIV ''challenge'' (through natural exposure) into a weaker challenge that a modest level of vaccine-induced immunity could overcome, preventing establishment of HIV infection or leading to a lower viral load and slower disease progression in the long term. Additionally, when given around the time of vaccination, PrEP might provide a protective ''cover'' if there is a transient period of enhanced susceptibility during and shortly after vaccination, followed by a period of immunity.…”
Section: Weaker Challenge Dose Favors Vaccine Protectionmentioning
confidence: 99%